2013
DOI: 10.4049/jimmunol.1202439
|View full text |Cite
|
Sign up to set email alerts
|

Host B7x Promotes Pulmonary Metastasis of Breast Cancer

Abstract: B7x (B7-H4 or B7S1) is an inhibitory member of the B7 family of T cell costimulation. It is expressed in low levels in healthy peripheral tissues such as the lung epithelium, but over-expressed in a variety of human cancers with negative clinical associations including metastasis. However, the function of B7x in the cancer context, whether expressed on cancer cells or on surrounding “host” tissues, has not been elucidated in vivo. We utilized the 4T1 metastatic breast cancer model and B7x knockout (B7x−/−) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…In an experimental model of lung metastasis, B7‐H4 expression by host cells was demonstrated to suppress tumor‐specific T‐cell responses and promote the infiltration of immunosuppressive T‐cell subsets into the lungs. As a result, B7‐H4 WT mice had more lung metastases than B7‐H4 knockout mice 28. Expression of B7‐H4 was also reported to show a correlation with tumor infiltration by Treg cells 29.…”
Section: Discussionmentioning
confidence: 97%
“…In an experimental model of lung metastasis, B7‐H4 expression by host cells was demonstrated to suppress tumor‐specific T‐cell responses and promote the infiltration of immunosuppressive T‐cell subsets into the lungs. As a result, B7‐H4 WT mice had more lung metastases than B7‐H4 knockout mice 28. Expression of B7‐H4 was also reported to show a correlation with tumor infiltration by Treg cells 29.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the activation of the B7-H4 signaling pathway may lead to tumor cells escaping from immune surveillance (Flies and Chen, 2007;Arigami et al, 2011;Sun et al, 2012). Recent report showed that host B7-H4 may enable metastasizing cancer cells to escape local antitumor immune responses through interactions with the innate and adaptive immune systems (Abadi et al, 2013). Several evidences have demonstrated that the B7-H4 molecule promotes cancer progression via regulating T cell mediated antitumor immunity (Zang et al, 2003;Sica et al, 2003;Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, B7-H4 has been reported to be highly expressed in human cancer cells, and their protein levels in tumors significantly correlate with patients' clinicopathological features and postoperative prognosis (Miyatake et al, 2007;Awadallah et al, 2008;Arigami et al, 2011;Abadi et al, 2013). However, no reports have investigated the clinical significance of B7-H4 expression in patients with thyroid cancer.…”
Section: Introductionmentioning
confidence: 97%
“…B7x binds activated T cells and inhibits T-cell functions. In addition, myeloid-derived suppressor cells (MDSCs) also express a receptor for B7x (30). Clinical data also support a coinhibitory function for B7x, as aberrant expression of this molecule is observed in many types of human cancers and is often associated with enhanced disease progression and poor clinical outcome (31).…”
mentioning
confidence: 92%